An Empirical Investigation on Nigeria’s External Debt Default: Implication for Domestic Debt Outstanding, External Reserve and Balance of Trade (1981 - 2015) - , Anyanwu Felicia Akujinma (Archives of Current Research International, 2016)
This study determines the long run association between external debt default, domestic debt outstanding, external reserve and balance of trade over a period of thirty five years from 1981 to 2015. The secondary data covering the period of the study were sourced from the Central Bank of Nigeria statistical bulletin. The stationarity test conducted on the variables via Augmented Dickey-Fuller (ADF) and Phillips Perron (PP) reveal that the variables were free from stationarity encumbrances in connection with most time series data. The Johansen co-integration test indicates the existence of a long run association between external debt default, domestic debt outstanding and external reserve but no evidence of a long run association between external debt default and Nigeria’s balance of trade. The granger effect assessment result suggests that external debt default has no significant effect on domestic debt outstanding, external reserve and balance of trade. Among the control variables introduced in the models, exchange rate was found to have significant effect on external reserve and it exhibits a positive and statistically relationship with balance of trade in short run but with external reserve in both long and short run. On the premises of the result of the analysis performed in this study, the government should as a matter of urgency diversify the economy from oil dependent to export oriented as was the case in the 1970s on the argument that a favourable and continually improved balance of trade position would lead to appreciation of the Naira against the US dollar, and an increase in the value of Naira on the other hand would encourage more exports by citizens which in turn lead to economic growth and development of Nigeria.